3D models of the bone marrow in health and disease: yesterday, today, and tomorrow. (25th September 2018) - Raic, Annamarija; Naolou, Toufik; Mohra, Anna; Chatterjee, Chandralekha; Lee-Thedieck, Cornelia
Abstract: Abstract : The complex interaction between hematopoietic stem cells (HSCs) and their microenvironment in the human bone marrow ensures a life-long blood production by balancing stem cell maintenance and differentiation. This so-called HSC niche can be disturbed by malignant diseases. Investigating their consequences on hematopoiesis requires a deep understanding of how the niches function in health and disease. To facilitate this, biomimetic models of the bone marrow are needed to analyze HSC maintenance and hematopoiesis under steady state and diseased conditions. Here, 3D bone marrow models, their fabrication methods (including 3D bioprinting), and implementations recapturing bone marrow functions in health and diseases are presented.